Impact of spontaneous tumor rupture on prognosis of patients with T4 hepatocellular carcinoma. Issue 7 (7th April 2016) - Chan, Wen‐Hui; Hung, Chien‐Fu; Pan, Kuang‐Tse; Lui, Kar‐Wai; Huang, Yu‐Ting; Lin, Shen‐Yen; Lin, Yang‐Yu; Wu, Tsung‐Han; Yu, Ming‐Chin
Abstract : Background and objectives: Compare the outcomes of three groups of patients with T4 hepatocellular carcinoma (HCC): tumor rupture with shock (RS group), tumor rupture without shock (R group), and no tumor rupture (NR group). Materials and Methods: We retrospectively reviewed 221 patients with T4 HCC from 2010 to 2012. The clinical background and prognosis were analyzed. Results: Overall in‐hospital mortality rate was 18.1%; overall median survival time was 4 months. The NR group were more likely to have multiple and infiltrative tumors ( P  < 0.001). Relative to the NR group, the R + RS group had better survival rates at 6 months (49.2% vs. 32.2%), 1 year (35.3% vs. 21.0%), 3 years (22.5% vs. 11.0%), and 5 years (17.7% vs. 5.5%) ( P  = 0.010). Patients in the RS group had a higher in‐hospital mortality rate, but significantly better long‐term survival than the NR and R group ( P  < 0.001). Multivariate analysis indicated that Child‐Pugh class B or C, presence of portal venous thrombosis, and absence of shock were significantly associated with poor survival. Conclusion: Patients with tumor rupture and shock had worse in‐hospital survival. However, patients without decompensated liver cirrhosis and portal venous thrombosis, and eligible for curative treatment had favorable long‐term outcome. J. Surg. Oncol. 2016;113:789–795 . © 2016 The Authors. Journal of Surgical Oncology Published by Wiley Periodicals, Inc.